The Professional Zakat Calculation System in Indonesia - Rodliyah, Nunung; Maharanny, Fegita (Yayasan Kawanad, 2025)
The professional zakat (income zakat) calculation system in Indonesia is stipulated by two authoritative sources: the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) Fatwa No. 3 of 2003, which states that professional zakat is calculated based on net income (after basic needs are deducted) annually; and the National Zakat Agency (Badan Amil Zakat Nasional/BAZNAS) Decree No. 1 of 2024, which stipulates that professional zakat is calculated based on gross income monthly and annually. This divergence presents a fundamental problem in the application of professional zakat in Indonesia. Therefore, this research aims to analyze the professional zakat calculation system from the perspective of both MUI and BAZNAS. This study employs an empirical-normative legal research method. Primary data were obtained through interviews, and secondary data were collected from primary, secondary, and tertiary legal materials, all analyzed qualitatively. The results indicate that professional zakat in Indonesia can be calculated from either net income (by deducting essential living expenses such as food, clothing, shelter, dependents’ needs including healthcare and education, and then paying 2.5% zakat if it reaches the nisab equivalent to 85 grams of gold annually), or from gross income (by paying 2.5% zakat at the time of income receipt, provided it meets the monthly nisab of IDR 6,859,349.00 or the annual nisab of IDR 82,312,725.00).